2000
DOI: 10.1126/science.287.5454.845
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Species Interactions Between Malaria Parasites in Humans

Abstract: The dynamics of multiple Plasmodium infections in asymptomatic children living under intense malaria transmission pressure provide evidence for a density-dependent regulation that transcends species as well as genotype. This regulation, in combination with species- and genotype-specific immune responses, results in nonindependent, sequential episodes of infection with each species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
156
3
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(177 citation statements)
references
References 35 publications
17
156
3
1
Order By: Relevance
“…A number of studies have reported that different species of the malaria agent Plasmodium in human blood suppress each other in mixed-infected individuals (e.g. Bruce et al 2000 ;Mayxay et al 2001), which may be mediated by cross-reactive IgM (Nagao et al 2008). Usually, the suppressed species rebounds after the other species has declined, and may appear as a prolonged infection (Richie, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported that different species of the malaria agent Plasmodium in human blood suppress each other in mixed-infected individuals (e.g. Bruce et al 2000 ;Mayxay et al 2001), which may be mediated by cross-reactive IgM (Nagao et al 2008). Usually, the suppressed species rebounds after the other species has declined, and may appear as a prolonged infection (Richie, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that in mixed infections in humans, cross-species or cross-genome interaction exists between malaria parasites. 2 A reduction in the severity of malaria symptoms occurs in individuals pre-exposed to different species, 3 and Plasmodium vivax infection may protect against the severe complications of P. falciparum. 2,4 This effect is thought partially to explain the lower mortality rates from P. falciparum seen in the AsiaPacific region compared with Africa.…”
Section: Discussionmentioning
confidence: 99%
“…2 A reduction in the severity of malaria symptoms occurs in individuals pre-exposed to different species, 3 and Plasmodium vivax infection may protect against the severe complications of P. falciparum. 2,4 This effect is thought partially to explain the lower mortality rates from P. falciparum seen in the AsiaPacific region compared with Africa. 5 A recent study has shown that sera from a volunteer experimentally infected with P. vivax suppressed the growth of P. falciparum in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies with semi-immune children in Papua Guinea, harbouring mixed infections by both Plasmodium species, have shown that parasite density of Plasmodium species in mixed infections oscillates around a threshold and that peaks of infection with each species do not coincide (Bruce et al 2000, Bruce & Day 2003. The authors proposed that malaria parasitaemia is controlled in a density-dependent manner in these semi-immune children by a cross-species parasite regulatory mechanism involving variant parasite antigens.…”
Section: Discussionmentioning
confidence: 90%